The Mill on the Floss - Eliot, George (Noida: Om Books International, 2019.)
First published in 1860, The Mill on the Floss is one of the most famous works by George Eliot, the pen-name adopted by Mary Ann Evans. Her most autobiographical work, it explores falling in love, tensions between siblings as well as the lack of intellectual freedom that Evans herself experienced. The story chronicles the life of Maggie Tulliver, who is robust, intelligent and fierce, and often in conflict with her family because of these traits. She seeks the cultured life of intense intellectual activity, represented by Philip Wakem, much to the disdain of her beloved brother Tom. The Mill on the Floss, a classic tale of unfulfilled love, growing up in distress and pain, and forgiveness, has been adapted to film and television. It remains one of Evanss most cherished works.
Keywords: Eliot, George, 1819-1880. Mill on the Floss; England - Fiction; Loss (Psychology) - Fiction